Utility of modified Faine’s criteria in diagnosis of leptospirosis - Bandara, Kanchana (BMC Infect Dis, 2016)
BACKGROUND: Leptospirosis is a globally emerging zoonotic disease and an important public health threat in developing countries. Diagnosis of leptospirosis is mainly based on clinical presentations in resource poor countries. World Health Organization (WHO) has introduced “Faine’s criteria” for diagnosis of leptospirosis. This study was conducted to evaluate the usefulness of modified Faine’s criteria (with amendment) 2012 to detect leptospirosis in resource poor settings. METHODS: Blood samples of 168 patients who fulfilled the inclusion criteria admitted between January 2013 to January 2014 were tested by a commercial immunochromatographic assay (Leptocheck WB, India), microscopic agglutination test (MAT) and polymerase chain reaction (PCR) methods. Leptospirosis was confirmed by a single MAT titre ≥1:400 and / or by a positive PCR. Diagnosis of leptospirosis was made using the clinical, epidemiological and laboratory data according to modified Faine’s criteria (with amendment) 2012. RESULTS: Leptospirosis was confirmed in 39 % (n = 66) by MAT and/or PCR. When modified Faine’s criteria (MAT ≥ 1.400 &/ or PCR), was evaluated against LERG confirmed cases sensitivity, specificity, positive predictive value and negative predictive values were 95.45 %, 56.86 %, 58.88 %, 95.08 % respectively. The modified Faine’s criteria with rapid immunochromatographic assay only had a sensitivity, specificity, positive predictive value and negative predictive value 89.39 %, 58.82 %, 58.42 %, and 89.55 % respectively. CONCLUSION: The modified Faine’s criteria which utilized only immunochromatographic assay (leptocheck IgM) in Part C was found to be useful tool for diagnosing leptospirosis in a resource poor setting.